An Attempt for the Measurement of Regional Competitiveness in Hungary - Miklos Lukovics; Imre Lengyel (European Regional Science Association (ERSA), 2006)
The main challenge of regional economic development is undoubtedly to increase the living standard and welfare of local population. Usually the state of development of regions and sub-regions within one country significantly differs. Parallel to the catching-up process of Hungary at the national level, there is another discernible process at the regional level: regional disparities are widening because the growth of the most developed sub-regions is increasing while the less favoured sub-regions are lagging behind. In Hungary, the dominates in development, the Western part is emerging, and the Eastern territorial units, mostly the ones by the boarder are lagging behind. Economic development should not be executed homogeneously, one should take into consideration the attributes and starting conditions of that certain territorial unit. The variety of starting conditions requires different interventions and strategies of economic development from region to region. Spatial units with different level of competitiveness should take variant steps on the road of economic development in order to achieve competitiveness in the global world. Due to their different starting conditions they cannot be developed by the same action plans. Regarding the fact that development or underdevelopment does not spread evenly in space, we chose to base our empirical research on the smallest spatial unit for which statistical data are still available. Furthermore sub-regions are worth analyzing because nowadays local economic development is attached to local areas and commuting zones that are almost equivalent to sub-regions. Present paper aims to rank the Hungarian sub-regions alongside development phases, with the help of multi-variable data analyzing methods based on a determined system of viewpoints, and adequate theoretical models and statistical data. We developed a weighting system of the indicators, following the logic of the adequate theoretical models. We are convinced that the presented theoretical model and the methodology based on it are suitable for making regional competitiveness measurable. Through this and with the help of statistical data, the competitiveness of any spatial unit of any level can be determined. We think what we have thon is significant because of the fact that a suitably analyzed starting point can contribute to choosing the best economic developing strategy for a certain region.
Keywords: 330